Broadband Communications, Networks, and Systems c - Tomkos, Ioannis; Bouras, Christos J.; Ellinas, Georgios; Demestichas, Panagiotis; Sinha, Prasun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International ICST Conference on Broadband Communications, Networks and Systems (BROADNETS 2010) held in October 2010 in Athens, Greece. The 39 revised full papers were carefully selected from numerous submissions. The conference was divided in 3 tracks: Optical, Wireless and Internet. The optical track covers topics such as optical switch architectures, reliable optical networking, routing, wavelength assignment, and traffic grooming, network control and management. The wireless track highlights MIMO and OFDM techniques, mobility management, routing protocols, hybrid networks and the internet track covers routing, scheduling, security, trust, semantic technologies and social networks.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Computers and Society; Software Engineering; Algorithm Analysis and Problem Complexity